Autoimmune pancreatitis: a case of difficult diagnosis - Cirocchi, Roberto; Santoro, Alberto; Corsi, Alessia; Ronca, Paolo; Desiderio, Jacopo; Barberini, Francesco; Boselli, Carlo; Noya, Giuseppe (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Autoimmune pancreatitis (AIP) is an insidious disease of non-specific symptomatology. To make correct diagnosis three different findings must correlate: radiological imaging, serological markers, and histology. This is not easy, and furthermore an incorrect diagnosis can lead to incorrect management and even patient death. We present our experience with a case of AIP in a young woman (34 years old) affected by different autoimmune pathologies with a history of abdominal pain. The diagnosis was made correlating histological findings and anamnestic data, although there were no radiological or serological findings. However, the management of this case was complicated by acute pancreatitis. In our case, we had only a histological sample and anamnestic data. So in these cases of positive history for autoimmune disorders and unclear clinical signs, AIP should be considered in differential diagnosis.